STRATEGI PEMASARAN PENJUALAN ONLINE DAN OFFLINE PADA PASAR TRADISIONAL DALAM PERSPEKTIF EKONOMI ISLAM - Nila Artika Dewi (PT. Habe Cendekia Utama, 2025)
This study aims to analyze online and offline sales marketing strategies applied in traditional markets, as well as evaluate the effectiveness of online marketing strategies in improving competitiveness amid the development of digital technology. Using a qualitative approach, this study was conducted in Pasar Umbul Kluwih, Pesawaran Regency, through the method of case studies, surveys, in-depth interviews, and Focus Group Discussions (FGD). The data collected is analyzed in a descriptive, comparative and qualitative way to provide a comprehensive overview of the marketing practices carried out by merchants. In addition, this study also examines the application of Islamic economic principles in marketing strategies, such as justice, honesty, and social welfare. The results showed that the combination of online and offline marketing strategies can increase the interaction between merchants and consumers, as well as make a positive contribution to sales. This study is expected to provide practical recommendations for traditional market traders in optimizing their marketing strategies, while maintaining values that are in accordance with Islamic economic principles.